Factors Affecting Career Preferences and Pathways: Insights from IT Students - Murimo Bethel Mutanga; Philip Xolisa Piyose; Sithembile Ndovela (Journal of Information System and Informatics, 2023)
The selection of an appropriate career path plays a pivotal role in shaping students' futures and can greatly enhance their employability prospects. By making well-informed decisions, students can align their educational pursuits with their professional aspirations, ensuring a seamless transition from academia to the workforce. This study aims to investigate the career choices of IT students within the Department of ICT. Through an analysis of the career choices made by students in these specific areas, the research seeks to uncover the underlying factors that influence their decision-making processes. By examining the career preferences of IT students, this research endeavor seeks to provide valuable insights into the motivations, interests, and aspirations that drive their choice of specialization. Additionally, it aims to explore how external factors, such as industry trends, job market demands, and personal experiences, impact their decision-making. Understanding these factors can offer valuable guidance to educational institutions, curriculum developers, and career advisors, enabling them to provide tailored support and guidance to IT students, thus facilitating more informed career decisions. Ultimately, the findings of this study will contribute to a better understanding of the career preferences and pathways within the IT field. This knowledge can aid educators and institutions in developing relevant and responsive curricula, fostering an environment that nurtures students' talents and equips them with the necessary skills and knowledge for their chosen career paths. Additionally, it can assist students in making informed choices that align with their passions and long-term goals, ultimately enhancing their employability and success in the dynamic and ever-evolving IT industry.